The correlation between total lymphocyte count and the number of candida colony from the oral cavity in HIV/AIDS patients (Medical Journal of Indonesia, 2005)
HIV infection causes qualitative and quantitative reduction of the T helper (Th) subset of T lymphocytes, facilitating opportunistic infection. One of the common opportunistic infections among HIV/AIDS patients is Candida infection in the oropharynx and esophagus. Detection of increased Candida colonialization is not always easy, CD4 count is a parameter that could be used as reference. The fact is there's only few laboratory can provide CD4 count. This study is a cross-sectional correlative study to determine the relation between total lymphocyte count as a much more applicable laboratory parameter and the intensity of Candida colonization in the oropharyngeal cavity of patients with HIV infection/AIDS. It was performed in the outpatient ward and inpatient ward of Dr. Cipto Mangunkusumo Hospital, from August 2004 to January 2005. The selected study subjects underwent interview, physical examination and had their blood samples and gargle samples taken. 60 study subjects were recruited, consisting of 52 males (86.7%) and 8 females (13.3%). The mean total lymphocyte count was 1194.53 cells/μL. Oropharyngeal candidiasis was found in 44 subjects (73.3%). There is a trend of higher Candida colonies number with lower total lymphocyte count despite no significant correlation between total lymphocyte count and the number of Candida colonies in the oral cavity of patients with HIV infection/AIDS. There is significant different between total lymphocyte count in positive and negative Candida colonies. (Med J Indones 2005; 14: 147-51)